Studies of the Canadian Arctic Archipelago water transport and its relationship to basin‐local forcings: Results from AO‐FVCOM. Issue 6 (25th June 2016) - Zhang, Yu; Chen, Changsheng; Beardsley, Robert C.; Gao, Guoping; Lai, Zhigang; Curry, Beth; Lee, Craig M.; Lin, Huichan; Qi, Jianhua; Xu, Qichun
Abstract: A high‐resolution (up to 2 km), unstructured‐grid, fully coupled Arctic sea ice‐ocean Finite‐Volume Community Ocean Model (AO‐FVCOM) was employed to simulate the flow and transport through the Canadian Arctic Archipelago (CAA) over the period 1978–2013. The model‐simulated CAA outflow flux was in reasonable agreement with the flux estimated based on measurements across Davis Strait, Nares Strait, Lancaster Sound, and Jones Sounds. The model was capable of reproducing the observed interannual variability in Davis Strait and Lancaster Sound. The simulated CAA outflow transport was highly correlated with the along‐strait and cross‐strait sea surface height (SSH) difference. Compared with the wind forcing, the sea level pressure (SLP) played a dominant role in establishing the SSH difference and the correlation of the CAA outflow with the cross‐strait SSH difference can be explained by a simple geostrophic balance. The change in the simulated CAA outflow transport through Davis Strait showed a negative correlation with the net flux through Fram Strait. This correlation was related to the variation of the spatial distribution and intensity of the slope current over the Beaufort Sea and Greenland shelves. The different basin‐scale surface forcings can increase the model uncertainty in the CAA outflow flux up to 15%. The daily adjustment of the model elevation to the satellite‐derived SSH in the North Atlantic region outside Fram Strait could produce a larger North Atlantic inflow through west Svalbard and weaken the outflow from the Arctic Ocean through east Greenland. Key Points: A high‐resolution Arctic Ocean FVCOM is capable of simulating the CAA outflow The basin‐scale sea level pressure is a major driver of the CAA outflow The volume flux through Davis Strait is negatively correlated with the flux through Fram Strait